Beerkan estimation of soil transfer parameters through infiltration experiments--BEST - Lassabatere, L; Angulo-Jaramillo, R; Soria Ugalde, J.M; Cuenca, R; Braud, I; Haverkamp, R (Soil Science Society of America journal, 2006)
Studying soil hydrological processes requires the determination of soil hydraulic parameters whose assessment using traditional methods is expensive and time-consuming. A specific method, Beerkan estimation of soil transfer parameters referred to as BEST was developed to facilitate the determination of both the water retention curve, theta(h), and the hydraulic conductivity curve, K(theta), defined by their shape and scale parameters. BEST estimates shape parameters from particle-size distribution analysis and scale parameters from infiltration experiments at null pressure head. Saturated water content is measured directly at the end of infiltration. Hydraulic conductivity and water pressure scale parameters are calculated from the steady-state infiltration rate and prior estimation of sorptivity (S). This is provided by fitting transient infiltration data on the classical two-term equations with values from zero to a maximum corresponding to null hydraulic conductivity and using a data subset for which the two-term infiltration equations are verified as valid. BEST was compared with other fitting methods to estimate sorptivity and hydraulic conductivity from infiltration modeling data on the basis of the same infiltration equations for three contrasting soils: agricultural soil, sandy soil, and a coarser fluvioglacial deposit. The other methods failed sometimes to model accurately experimental data and to provide values in agreement with physical principles of water infiltration (negative values for hydraulic conductivity, too high steady-state infiltration rate). None of these anomalies was encountered when modeling cumulative infiltration with BEST. BEST appears to be a promising, easy, robust, and inexpensive way of characterizing the hydraulic behavior of soil.